DNA methylation in Parkinson's disease. (10th June 2016) - Wüllner, Ullrich; Kaut, Oliver; deBoni, Laura; Piston, Dominik; Schmitt, Ina
Abstract: Epigenetic processes control the embryonic development into multicellular organisms and determine the functional differences of genetically identical cells and individuals. They are also involved in a variety of complex functions such as learning and memory consolidation and have been implicated in aging processes. Beyond the actual genetic information encoded in the DNA sequence, epigenetic modifications in particular DNA methylation and various histone modifications shape the chromatin into a transcriptional permissive or repressive state. DNA methylation patterns are altered by environmental conditions and can be carried forward through mitosis and meiosis. Hence, DNA methylation probably mediates complex environment–gene interactions, determines individual disease characteristics, and contributes to effects and side effects of drugs. In addition to classic monogenic epigenetic diseases, i.e., Prader‐Willi and Rett syndrome, recent data point to an epigenetic component also in apparent sporadic neuro‐psychiatric disorders and increasing evidence suggests a role for altered DNA methylation in Parkinson's disease. Epigenetic alterations, DNA methylation in particular, may account for the yet unexplained individual susceptibility and the variability in the course of Parkinson's disease and could provide hints toward the development of novel therapeutic targets. Parkinson's disease (PD) is conceptualized as a consequence of genetic variants and environment–gene interactions on a background of age‐related changes. Epigenetic modifications have been implicated in aging and can be altered by environment stimuli. The review explores the possibility of an epigenetic component in PD, focusing on DNA methylation. Methylation of α‐synuclein ( SNCA ) and microtubule‐associated protein tau gene appear to be of particular importance and epigenome‐wide methylation studies point to several additional candidate genes which may contribute to the individual susceptibility toward PD. This article is part of a special issue on Parkinson disease . Abstract : Parkinson's disease (PD) is conceptualized as a consequence of genetic variants and environment–gene interactions on a background of age‐related changes. Epigenetic modifications have been implicated in aging and can be altered by environment stimuli. The review explores the possibility of an epigenetic component in PD, focusing on DNA methylation. Methylation of α‐synuclein ( SNCA ) and microtubule‐associated protein tau gene appear to be of particular importance and epigenome‐wide methylation studies point to several additional candidate genes which may contribute to the individual susceptibility toward PD. This article is part of a special issue on Parkinson disease .